(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2015)
An experimental study was done to observe the hypocholesterolaemic effect of wheatgrass (Triticum aestivum) juice on experimentally induced hypercholesterolaemic rats, especially on serum low density lipoprotein (LDL) level, which was carried out in the Department of Pharmacology & Therapeutics, Dhaka Medical College, Dhaka, between July, 2009 and June, 2010. A total number of 48 healthy adult male Long Evans rats (Norwegian strain) were used for the present study. 6 rats were taken in each group of total 8 groups treated differently with 1 control group. Rats of the first 5 groups were sacrificed at 29th day and their serum total cholesterol levels were measured. The rest of the rats were sacrificed at 57th day and their serum total cholesterol levels were measured. The mean serum LDL of 10ml/kg grass juice fed normal rats was decreased by 11.64% than that of the laboratory diet fed control group (P<0.01). Serum LDL of the group of rats treated with 10ml/kg grass juice and1% cholesterol diet were decreased by 36.59% than that of the hypercholesterolaemic control group (P<0.001). Serum LDL of the hypercholesterolaemic rats treated with 10ml/kg grass juice for 28 days were decreased by 29.10%, and in hypercholesterolaemic rats treated with 20ml/kg grass juice for 28 days were decreased by 39.46% (P<0.001). Reduction of LDL as evident on hypercholesterolaemic rats treated with 20ml/kg grass juice, which was similar to hypercholesterolaemic rats treated with 0.14mg/kg Atorvastatin for 28 days. DOI: http://dx.doi.org/10.3329/bjpp.v30i2.22678 Bangladesh J Physiol Pharmacol 2014; 30(2): 18-24